Clinical evaluation after matrix-associated autologous chondrocyte transplantation: a comparison of four different graft types. Issue 7 (1st July 2021) - Binder, Harald; Hoffman, Lukas; Zak, Lukas; Tiefenboeck, Thomas; Aldrian, Silke; Albrecht, Christian
Abstract : Aims: The aim of this retrospective study was to determine if there are differences in short-term clinical outcomes among four different types of matrix-associated autologous chondrocyte transplantation (MACT). Methods: A total of 88 patients (mean age 34 years (SD 10.03), mean BMI 25 kg/m 2 (SD 3.51)) with full-thickness chondral lesions of the tibiofemoral joint who underwent MACT were included in this study. Clinical examinations were performed preoperatively and 24 months after transplantation. Clinical outcomes were evaluated using the International Knee Documentation Committee (IKDC) Subjective Knee Form, the Brittberg score, the Tegner Activity Scale, and the visual analogue scale (VAS) for pain. The Kruskal-Wallis test by ranks was used to compare the clinical scores of the different transplant types. Results: The mean defect size of the tibiofemoral joint compartment was 4.28 cm 2 (SD 1.70). In total, 11 patients (12.6%) underwent transplantation with Chondro-Gide (matrix-associated autologous chondrocyte implantation (MACI)), 40 patients (46.0%) with Hyalograft C (HYAFF), 21 patients (24.1%) with Cartilage Regeneration System (CaReS), and 15 patients (17.2%) with NOVOCART 3D. The mean IKDC Subjective Knee Form score improved from 35.71 (SD 6.44) preoperatively to 75.26 (SD 18.36) after 24 months postoperatively in the Hyalograft group, from 35.94 (SD 10.29) to 71.57 (SD 16.31) in the Chondro-Gide (MACI) group, from 37.06 (SD 5.42) to 71.49 (SD 6.76) in the NOVOCART 3D group, and from 45.05 (SD 15.83) to 70.33 (SD 19.65) in the CaReS group. Similar improvements were observed in the VAS and Brittberg scores. Conclusion: Two years postoperatively, there were no significant differences in terms of outcomes. Our data demonstrated that MACT, regardless of the implants used, resulted in good clinical improvement two years after transplantation for localized tibiofemoral defects. Cite this article: Bone Joint Res  2021;10(7):370–379.